PHYSICAL AND CHEMICAL EVALUATIONS OF TOPICAL RADIANCE SERUM CONTAINING NANOEMULSION COMBINATION OF ASTAXANTHIN AND ZEAXANTHIN: DESIGNED AS ANTI-WRINKLE AND SKIN-BRIGHTENING SERUM - NURDIANTI, LUSI; SETIAWAN, FAJAR; RUSDIANA, TAOFIK; GOZALI, DOLIH; CAHYATI, KENI IDA (International Journal of Applied Pharmaceutics, 2023)
Objective: The present study was conducted to formulate and evaluate the radiance serum containing the combination of astaxanthin and zeaxanthin nanoemulsion designed for anti-wrinkle and skin brightening serum by topical route of administration. Methods: The nanoemulsion containing astaxanthin and zeaxanthin was prepared using the self-nano emulsifying method, followed by incorporation into the radiance serum by the conventional mixing method. The quantity and ratio of surfactant, co-surfactant, and oil phase have been optimized in the previous study, as well as the radiance serum formula. The evaluation of the nanoemulsion and radiance serum was carried out by physical and chemical characterization. At the end of the study, an antioxidant activity of the serum containing nanoemulsion of astaxanthin and zeaxanthin was performed by DPPH method and the antioxidant activity was compared to its pure forms. The evaluation of the ex vivo permeation study was carried out to evaluate its possibility as an anti-wrinkle and skin brightener. Results: An astaxanthin and zeaxanthin nanoemulsion had a good physical properties with a globule size around of 20 nm (narrow particle size distribution), an entrapment efficiency range greater than 85%, and had a spherical morphology. The radiance serum had a good organoleptic and spreadability with the semifluid characteristic. Based on the result of antioxidant activity, the radiance serum had a highly active antioxidant activity. The radiance serum contained of astaxanthin and zeaxanthin nanoemulsion of 1% concentration, astaxanthin had a 2-6 times cumulative released compared than zeaxanthin (p<0.05) and all of the formulations exhibited a high skin permeation significantly. Conclusion: A formulation of nanoemulsion-based serum containing astaxanthin and zeaxanthin for topical delivery has been successfully developed. Based on the results of physical evaluation and especially from the permeation study, it seems that radiance serum containing astaxanthin and zeaxanthin nanoemulsion was potential to be used as an anti-wrinkle and skin brightening, however this function must be proven in further research.